Structural and electrochemical properties of Wollastonite-Based Chemically Bonded Phosphate Ceramic coatings. Issue 7 (1st April 2021) - Yan, Ge; Wang, Mingyang; Sun, Tao; Li, Xinping; Xu, Fang; Tian, Kun; Yin, Weisong
Abstract: An inorganic anticorrosive coating, merging wollastonite into Chemically Bonded Phosphate Ceramic (CBPC) binders, was prepared to protect rebar from corrosion. In order to evaluate the corrosion resistance behavior of Wollastonite-based Chemically Bonded Phosphate Ceramic (WoCBPC) coatings, the electrochemical measurements were applied. The experiment results showed that the value of corrosion potential (Ecorr ) and polarization resistance (Rp ) is the largest and the value of corrosion current density (Icorr ) is the smallest among all WoCBPC coatings, when the content of wollastonite reaches 20% of the ceramic filler (WoCBPC20). Moreover, the resistance of WoCBPC20 coating (Rc ) value was much higher than that of other WoCBPC coatings, which means the best anticorrosion properties. The structure formation of WoCBPC coatings was identified by using XRD as well as SEM/EDS techniques. The intensity of berlinite phase reaches the maximum with the introduction of wollastonite in WoCBPC20 coatings. Meanwhile, the fibrous wollastonite particles with high modulus can inhibit the spread of cracks in CBPC matrix. Therefore, the WoCBPC coatings show a barrier effect to prevent aggressive substances from contacting the rebar effectively.